2022
DOI: 10.1007/s12975-022-01039-y
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps (NETs): A New Therapeutic Target for Neuroinflammation and Microthrombosis After Subarachnoid Hemorrhage?

Abstract: Neutrophil extracellular traps (NETs) play a major role in intrinsic immunity by limiting and killing pathogens. Recently, a series of studies have confirmed that NETs are closely associated with vascular injury and microthrombosis. Furthermore, NETs play an important role in neuroinflammation after ischemic and hemorrhagic stroke. Neuroinflammation and microthrombosis after subarachnoid hemorrhage are key pathophysiological processes associated with poor prognosis, but their crucial formation mechanisms and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
(11 reference statements)
1
8
0
Order By: Relevance
“…Extensive microthrombosis induced by specific triggers can lead to tissue damage, impairment of organ blood supply and, ultimately, organ failure 22 . Microthrombosis is associated with the formation of numerous neutrophil extracellular traps (NETs) in sepsis 23 . DNA enzymes (DNase) in normal human blood are capable of degrading NETs, but when infection occurs, large amounts of NETs are released into the blood, resulting in the activation of endogenous and exogenous coagulation pathways and platelets, thus promoting microthrombosis 24–26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive microthrombosis induced by specific triggers can lead to tissue damage, impairment of organ blood supply and, ultimately, organ failure 22 . Microthrombosis is associated with the formation of numerous neutrophil extracellular traps (NETs) in sepsis 23 . DNA enzymes (DNase) in normal human blood are capable of degrading NETs, but when infection occurs, large amounts of NETs are released into the blood, resulting in the activation of endogenous and exogenous coagulation pathways and platelets, thus promoting microthrombosis 24–26 .…”
Section: Discussionmentioning
confidence: 99%
“…22 Microthrombosis is associated with the formation of numerous neutrophil extracellular traps (NETs) in sepsis. 23 DNA enzymes (DNase) in normal human blood are capable of degrading NETs, but when infection occurs, large amounts of NETs are released into the blood, resulting in the activation of endogenous and exogenous coagulation pathways and platelets, thus promoting microthrombosis. [24][25][26] Therefore, in this study, we investigated the effects of GA on multiple organ Geldanamycin was first found to have antiprotozoal and antitumor effects by Sasaki et al 27 Later, good antiviral activity of GA was also found.…”
Section: Discussionmentioning
confidence: 99%
“…When the microthrombi fill microvessels 22 and the glymphatic drainage system, 23 the whole microcirculation collapses without blood flow, and microcirculation dysfunction moves into an irreversible phase. Recent findings involving neutrophil extracellular traps (NETs) 24 released from neutrophils after SAH might be the core intersections among platelet aggregation, microthrombosis, and microglia-mediated inflammation, 25 further supporting the pathophysiological characteristics of the irreversible phase of microcirculation. 26 , 27 …”
Section: Intersections In the Pathophysiological Changes Induced By T...mentioning
confidence: 86%
“…When the microthrombi fill microvessels 22 and impair the glymphatic drainage system, 23 the whole microcirculation collapses without blood flow, and microcirculatory dysfunction moves into an irreversible phase. Recent findings involving neutrophil extracellular traps (NETs) 24 released from neutrophils after SAH might represent important intersections amongst platelet aggregation, microthrombosis, and microglia-mediated inflammation, 25 further supporting the pathophysiological characteristics of the irreversible phase of microcirculation. 26,27 Hypoxia aggravates pathophysiological changes after bleeding into the CSF It is well known that the vast majority of patients lack ischaemic lesions in brain imaging at the early phase of SAH; even in limited cohorts with poor-grade ruptured aneurysms, only approximately 21% of patients suffer from cerebral infarction.…”
Section: Intersections In the Pathophysiological Changes Induced By T...mentioning
confidence: 88%
“…In addition, recent research has shown that neutrophil-released neutrophil extracellular traps (NETs) play important roles in both thrombosis and trapping invading microorganisms [ 173 , 174 ]. In response to the stimulus of injury, a large meshwork of structures containing histones, DNA, and granule proteins, among others [ 175 ], is formed, and this meshwork may be a central crossroads of platelet aggregation, microthrombosis, and microglia-mediated inflammation [ 176 , 177 ] and thus play an important role in irreversible impairment of the microcirculation [ 178 ].…”
Section: Infiltration Of Peripheral Inflammatory Cells and Their Cros...mentioning
confidence: 99%